The Role of the German Armed Forces in the Finnish War of Independence in 1918 - Kari Alenius (Acta Historica Universitatis Klaipedensis)
The Grand Duchy of Finland was the first region to declare independence from the Russian Empire in the final stages of the First World War. However, the declaration of independence in December 1917 was insufficient, and Finland fought a war of independence until the country’s sovereignty and its democratic political system were finally secured. The fiercest phase of the war was in the spring of 1918. The main parties were, on one hand, the Finnish left, which received support from the Russian Bolsheviks, and on the other hand, the non-socialist groups supported by Germany. The German armed forces played a significant role in the fact that the war ended with the victory of the Finnish democratic government. Previous research has investigated thoroughly the details of the military operations by the German forces, but the role and importance of the German armed forces in the overall picture of the war has received relatively little attention. This article analyses in more detail what kind of contribution the German troops made. There are indications that their importance was greater than most scholars have estimated.